Arts-based research methods in writing studies : a primer - Hanzalik, Kate, 1981- (Routledge, 2021)
"Arts-Based Research Methods in Writing Studies offers a concise guide for writing studies scholars and other allied fields that addresses the skepticism, possibilities, and performances of Arts-Based Research (ABR). Debunking the field's resistance to art as a way of knowing, the book defines the arts-based qualitative paradigm and shows how it is already being reflected in the increasingly popular arts-based movement in writing studies. Using ABR methods of data collection and representation, the book offers an insightful case study of the composing processes and cultural contexts of refugee artists in the Sanctuary City of Syracuse, to explore themes and research questions about the connections between art and writing, how expert artists offer insight into best practices for collaborative composing, commitment to achieving a purpose, negotiating traditional techniques for current contexts, improvising, and creating with limited resources. Addressing ethical considerations and practices in research while demonstrating that ABR can provide strategies for writing studies scholars to contribute to marginalized peoples, the book discusses its pedagogical applications in a range of contexts. This book will be an important resource for scholars and graduate students in writing studies and those interested in literacy studies, transnational literacies, rhetoric, composition, first-year writing, critical writing, border rhetorics, writing centers, writing across the curriculum, writing in the disciplines, and translingualism"--